Swine Manure Management - James P Murphy (Kansas Agricultural Experiment Station Research Reports, 1996)
Manure nutrients help build and maintain soil fertility. Manure also improves tilth, increases waterholding capacity, lessens wind and water erosion, improves aeration, and promotes beneficial organisms. When wastes include runoff or dilution water, they can supply water as well as nutrients to crops. The economic value of manure fertilizer is calculated from its available nitrogen (N), phosphorus (P), and potassium (K) at commercial fertilizer prices. These values change with the costs of fertilizer and handling practices.; Swine Day, Manhattan, KS, November 21, 1996
Keywords: Swine day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 772; Swine; Manure management